2010
DOI: 10.1093/hmg/ddq519
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-132 orchestrates chromatin remodeling and translational control of the circadian clock

Abstract: Mammalian circadian rhythms are synchronized to the external time by daily resetting of the suprachiasmatic nucleus (SCN) in response to light. As the master circadian pacemaker, the SCN coordinates the timing of diverse cellular oscillators in multiple tissues. Aberrant regulation of clock timing is linked to numerous human conditions, including cancer, cardiovascular disease, obesity, various neurological disorders and the hereditary disorder familial advanced sleep phase syndrome. Additionally, mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 64 publications
7
132
1
2
Order By: Relevance
“…In contrast to PTEN and RASA1, we did not detect any differences in transcript levels of the antiproliferative factor, BTG2, between DO and L follicles. BTG2 is a bonafide target of miR-21 and miR-132 in mouse and human cells respectively (Alvarez-Saavedra et al 2011. Although only limited amounts of granulosa cells could be collected from individual follicles in live mares, which precluded analyses of protein levels in these samples, we cannot exclude a potential miRNA effect on levels of BTG2 protein.…”
Section: Mirnas In Equine Folliclesmentioning
confidence: 96%
“…In contrast to PTEN and RASA1, we did not detect any differences in transcript levels of the antiproliferative factor, BTG2, between DO and L follicles. BTG2 is a bonafide target of miR-21 and miR-132 in mouse and human cells respectively (Alvarez-Saavedra et al 2011. Although only limited amounts of granulosa cells could be collected from individual follicles in live mares, which precluded analyses of protein levels in these samples, we cannot exclude a potential miRNA effect on levels of BTG2 protein.…”
Section: Mirnas In Equine Folliclesmentioning
confidence: 96%
“…111 miR-132, which is dysregulated in schizophrenia and is involved in antiviral innate immunity and circadian timing, has been to shown regulate gene expression by directly inhibiting DNMT3A, the transcription factor GATA2, EP300 (a transcriptional co-activator), as well as several members of histone modifying complexes in vitro and in vivo. [112][113][114] Endo-siRNAs may also be involved in de novo DNA methylation, as seen with the A. thaliana gene FWA. In this case the process appears to occur in two steps, including initial recruitment of siRNAs to pre-methylated FWA and then either cis-or trans-directed DNA methylation of transgenic copies introduced by transformation with Agrobacterium.…”
Section: Epigenetic Mechanisms Of Short Ncrnasmentioning
confidence: 99%
“…Thus, miR-132 levels can modulate the negative arm of the circadian clock and the response of the molecular circadian machinery to light. In a follow-up study, Alvarez-Saavedra et al [61] showed that miR-132 controls the molecular clock in response to light by targeting a specific set of chromatin and translational regulators. The chromatin regulator Mecp2 is involved in the expression of the per1 and per2 promoters, and the proteins Btg2 and Paip2a suppress production of PER1 and PER2 by accelerating mRNA decay.…”
Section: Rspbroyalsocietypublishingorg Proc R Soc B 280: 20130011mentioning
confidence: 99%